Effect of electroacupuncture on restoration of traumatic vertebral compression fracture: two case studies and literature review - Yeum, Ji-Sung; Yun, Ye-Rim; Kim, No-Hyun; Choi, Jong-Ho; Kim, Do-Young (Frontiers in Medicine, 2025)
Vertebral compression fractures (VCFs) cause severe pain and functional impairments. Conventional treatments, including medication and vertebral augmentation, have limited efficacy and safety. Electroacupuncture (EA), which combines acupuncture with electrical stimulation, is a promising but under-studied approach for VCF management. This case report with a literature review presents two cases of traumatic VCF that were successfully treated with EA as well as a literature review on this topic. Two female patients with acute VCFs were assessed using the Numerical Rating Scale (NRS), Oswestry Disability Index (ODI), and EuroQol-5 Dimension (EQ-5D) at baseline and at 2 and 4 weeks post-treatment. EA was applied to the deep paraspinal muscles using stainless steel needles (0.30 × 60 mm) inserted up to 50 mm, with 4-Hz, 1–2-mA stimulation for 20 min, twice daily. Adjunctive treatments included analgesics, herbal medicines, and thermotherapy. A literature review was conducted to determine the efficacy of EA in fracture recovery. Both patients experienced marked pain relief and functional improvements. Their NRS scores decreased from 70 to 40 (patient 1) and 30 (patient 2), ODI scores decreased from ∼85 to 64.4 and 42.2, respectively, and EQ-5D scores improved to 67.7 (patient 1) and 73.0 (patient 2). Early restoration of standing ability and ambulation was also observed. The findings from the literature review suggest that EA may enhance bone healing via callus formation and immune modulation. EA applied to the deep paraspinal muscles may be an effective, minimally invasive treatment for VCF, promoting pain relief and recovery. Further controlled trials are required to confirm the efficacy and mechanism of action.